Dukungan Keluarga dan Kesiapan Kerja di Kalangan Siswa SMK di Indonesia: Efek Mediasi dari Wawasan Dunia Kerja - Rohman, Mojibur; ., Marji; Sudjimat, Dwi Agus; Sugandi, R Machmud (UNIVERSITAS PENDIDIKAN GANESHA, 2022)
Abstrak Kesiapan kerja siswa kejuruan di Indonesia menjadi salah satu isu penting yang terus dibahas. Hal tersebut dikarenakan lulusan pendidikan kejuruan tersebut masih menduduki posisi teratas untuk angka pengangguran dibandingkan tingkat pendidikan yang lain. Rendahnya kesiapan kerja di kalangan siswa dipengaruhi oleh banyak faktor yang perlu diidentifikasi. Penelitian ini bertujuan untuk menguji secara empiris pengaruh dukungan keluarga terhadap kesiapan kerja siswa kejuruan yang dimediasi oleh wawasan dunia kerja. Untuk itu 115 siswa dipilih melalui teknik cluster random sampling dari 4 SMK yang ada di Jawa Timur, Indonesia. Pengumpulan data menggunakan kuesioner untuk mengukur skala dukungan keluarga, wawasan dunia kerja dan kesiapan kerja siswa. Pengujian hipotesis dilakukan dengan analisis jalur pada tingkat signifikansi 0,05. Hasil penelitian menujukkan bahwa dukungan keluarga berpengaruh signifikan terhadap kesiapan kerja siswa, baik secara langsung maupun tidak langsung melalui wawasan dunia kerja. Dengan demikian, keterlibatan keluarga harus maksimal dalam memberikan dukungan yang dibutuhkan oleh siswa. Di sisi lain, sekolah harus mampu menyediakan informasi pekerjaan yang tepat untuk membantu siswa dalam memperluas wawasan mereka tentang dunia kerja.Kata kunci: kesiapan kerja; dukungan keluarga; wawasan dunia kerja; SMK. AbstractJob readiness of vocational students in Indonesia is one of the important issues that continues to be discussed. This is because vocational education graduates still occupy the top position for unemployment rates compared to other levels of education. The low job readiness among students is influenced by many factors that need to be identified. This study aims to empirically examine the effect of family support on vocational students' job readiness mediated by the world of work insight. For this reason, 115 students were selected through a cluster random sampling technique from 4 vocational schools in East Java, Indonesia. Collecting data using a questionnaire to measure the scale of family support, insight into the world of work and student work readiness. Hypothesis testing was carried out by path analysis at a significance level of 0.05. The results of the study show that family support has a significant effect on students' work readiness, both directly and indirectly through insight into the world of work. Thus, family involvement should be maximized in providing the support needed by students. On the other hand, schools must be able to provide appropriate job information to assist students in broadening their horizons about the world of work.Keywords : working readiness; family support; insight into the world of work; SMK.DAFTAR RUJUKANSuswanto, H., Asfani, K., and Wibawa, A.P. (2017). Contribution of teaching performance, learning satisfaction and achievement motivation to students’ competence achievement. Global J. of Engng. Educ., 19, 1, 66-71.Billett, S. (2011). Vocational Education Purposes, Traditions and Prospects. New York: Springer,.Pavlova, M. (2009). Technology And Vocational Education For Sustainable Development : Empowering Individuals for the Future. Queensland: Springer.Badan Pusat Statistik (BPS), Tingkat Pengangguran Terbuka (TPT) sebesar 5,34 persen (2018), 14 May 2019, https://www.bps.go.id/pressrelease/2018/11/05/1485/agustus-2018–tingkat-pengangguran-terbuka–tpt–sebesar-5-34-persen.htmlSasmito, A.P., Kustono, D. & Patmanthara, S. (2015). Kesiapan Memasuki Dunia Usaha/Dunia Industri (DU/DI) Siswa Paket Keahlian Rekayasa Perangkat Lunak di SMK. Teknologi dan Kejuruan, 38, 1, 25-40.Caballero, C., Walker, A., & Fuller-Tyszkiewicz, M. (2011). The Work Readiness Scale (WRS): Developing a measure to assess work readiness in college graduates. J. of Teaching and Learning for Graduate Employability, 2, 2, 41-54.Caballero, C., & Walker, A. (2010). Work readiness in graduate recruitment and selection: A review of current assessment methods. J. of Teaching and Learning for Graduate Employability, 1, 1, 13- 25.Setyawati, R., (2017). Pengaruh Pengalaman Praktik Kerja Industri, Pelaksanaan Bimbingan Kejuruan dan Dukungan Keluarga terhadap Kesiapan Kerja Siswa SMK Swasta di Kabupaten Bantul. Jurnal Sosial Humaniora dan Pendidikan, 2, 1, 36-45.Grant, K.B. & Ray, J.A., (2010). Home, School, and Community Collaboration. United Stae of America: SAGE Publication, Inc.,King, R.B., & McInerney, D.M., (2019). Family-support goals drive engagement and achievement in a collectivist context: Integrating etic and emic approaches in goal research. Contemporary Educational Psychology 58, 338-353.Igberadja, S., (2015). Factors Influencing Performance In Basic Technology Among Secondary School Students of Delta South Senatorial District in Delta State, Nigeria, Journal of Technical Education and Training (JTET), 7, 2, 24-34.Odo, M. I. (2015). Sustaining Occupational Information for Career Choice and Development in Students of Technical Colleges in Enugu State, Nigeria. Journal of Technical Education and Training (JTET), 7, 1, 1-9.Saniter, N., Schnitzlein, D.,D., & Siedler, T. (2019). Occupational Knowledge and Educational Mobility: Evidence from the Introduction of Job Information Centers. Economics of Education Review, 69, 108-124.Feldt, L.S., & Brennan, R.L., (1989). Reliability educational measurement. New York: McMillan Publishing Company.Isarabhakdi, P. & Pewnil, T. (2016). Engagement with family, peers, and Internet use and its effect on mental well-being among high school students in Kanchanaburi Province, Thailand, International Journal of Adolescence and Youth, 21, 1, 15-26.Smitsa, J. & Hosgor, A.G. (2006). Effects of family background characteristics on educational participation in Turkey, International Journal of Educational Development, 26, 545-560.Ismail, M.E., Hashim, S., Hamzah, N., Samad, N.A., Masran, S.M., Mat Daud, K.A., Amin, N.F.M.,, Samsudin, M.A. & Kamarudin, N.Z.S. (2019). Factors that Influence Students’ Learning: An observation on Vocational College students, Journal Of Technical Education And Trainin, 11, 1, 93-99.Ainane, S., Bouabid, A. & Sokkary, W.E. (2019). Factors that influence the high percentage of women enrolled in engineering in the UAE and preparing for careers in the oil and gas industry, Global Journal of Engineering Education., 21, 1, 62-68.